Answer:
x = 3
y = -1
Step-by-step explanation:
Based on the fact that our have two variables and two equations, I'm going to assume you are trying to find the values of x and y.
For these two equations, let's first find the value of x using the equation elimination method.
We're going to eliminate the y variable by multiplying the first equation by 2 and then adding that new equation to the second equation.
7x - y = 22 ==> 14x - 2y = 44
4x + 2y + (14x - 2y) = 10 + (44)
18x + 0y = 54
x = 3
Now we plug the value of x back into one of the equations to find the value of y.
7x - y = 22
7(3) - y = 22
-y = 22 - 21
y = -1
So our values are as follows:
x = 3
y = -1
Cheers.